EVALUATION AND OPTIMIZATION OF NATURAL LIGHTING ON THE SECOND FLOOR OF THE LAMPUNG HAPKIDO MARTIAL ARTS ROOM AT BTC (BAGOES TRAINING CENTER) GYM SEPUTIH RAMAN : EVALUASI DAN OPTIMALISASI PENCAHAYAAN ALAMI PADA LANTAI DUA RUANG BELADIRI HAPKIDO LAMPUNG DI BTC (BAGOES TRAINING CENTER) GYM SEPUTIH RAMAN - Berlian Chandra Kirana; Tiara Chandra Kirani; Sefrani I G Siregar; Ahmad Suaif; Himawan Wismanadi; Aghus Sifaq (SOSIOEDUKASI, 2025)
The light source that comes from sunlight entering directly into the room, especially in the morning and afternoon, is called natural lighting. SNI 03-2396-2001 states that ideal natural lighting during the day, from 08:00 to 16:00 WIB, should provide evenly distributed light throughout the room without causing glare. The standard illumination for martial arts training rooms ranges from 300 lux (minimum), 350 lux (medium), and 500 lux (maximum). The aim of the research is to evaluate and optimize natural lighting in sports spaces, particularly the Hapkido room on the second floor of the BTC (Bagoes Training Center) Gym in Seputih Raman, Lampung. The quality, orientation of window openings, and the distribution of light entering the building through windows are important factors in utilizing natural lighting. With larger window sizes, there is a need to control the amount of light entering the room. A quantitative method is used in this research. Data is collected through observation, literature review, light intensity measurements in the field, and simulations of current conditions using DIALux Evo. Data analysis uses mathematical formulas. The results show that lighting at BTC (Bagoes Training Center) Gym lacks light intensity and does not meet the standard. As a result, athletes feel less comfortable during training. At BTC Gym, lighting intensity has been adjusted to meet the lighting standards through several changes, such as lowering glass reflectance, altering window sizes, changing the type of window glass, and reducing sun shading. The lighting level has been improved, and the room now meets the SNI 03-2396-2001 standard. The Daylight Factor should be between 2% and 5%, with TUU between 0.5 and 0.8, and TUS between 0.3 and 0.5. A Daylight Factor above 10% can cause glare, uneven light distribution, and excessive heating, which requires design modifications to ensure optimal natural lighting.